Biophysical and Chemical Properties of Collagen : Biomedical Applications - Ramshaw, John A. M.; Glattauer, Veronica (IOP Publishing, 2020)
Collagen has proved to be a safe and effective biomedical material. Clinicians have used collagen-based devices in a wide range of applications with successful patient outcomes. This book gives an understanding of how present devices work, and could be improved, as well as the development of new devices where a knowledge of collagen structure, chemistry and biology is required. The purification of collagen materials and the fabrication of a range of collagen products and their applications are covered within. Current developments include recombinant collagen materials that provide further application opportunities. Written by experts in the field, this text will be of interest for researchers as well as lecturers and students. Part of Biophysical Society Series.
Keywords: Biomedical materials.; elektronické knihy; electronic books